Structural, electrical and optical properties of hetrostructured MoS2/ZnO thin films for potential perovskite solar cells application - M.I. Khan; Sabir Ali; Norah Alwadai; Ikram-ul-Haq; Muhammad Irfan; Hind Albalawi; Aljawhara H. Almuqrin; Maha M. Almoneef; Munawar Iqbal (Journal of Materials Research and Technology, 2022)
ZnO, MoS2, MoS2/ZnO/glass, and ZnO/MoS2/glass thin films have been deposited on glass substrates by chemical bath deposition techniques (CBD). XRD results confirmed the formation of MoS2, ZnO, MoS2/ZnO/glass, and ZnO/MoS2/glass films. All the films have a hexagonal structure. The grain size of heterostructured (MoS2/ZnO/glass and ZnO/MoS2/glass) films is larger than pure (ZnO and MoS2) films. The band gap energy of ZnO, MoS2, MoS2/ZnO/glass and ZnO/MoS2/glass is 3.14 eV, 1.52 eV, 1.62 eV and 2.67 eV, respectively. Photoluminescence (PL) emission peaks of ZnO are observed in the visible region. When ZnO film is deposited on MoS2 film, PL peaks are shifted to smaller wavelengths. A very high PL intensity peak of MoS2 is observed. When MoS2 film was deposited on ZnO film the peak intensity was reduced. The average sheet resistivity of glass/MoS2, glass/ZnO, MoS2/ZnO/glass and ZnO/MoS2/glass films is 6.44 × 104, 7.89 × 103, 5.65 × 104, and 2.45 × 103 (ohm-m), respectively. These materials have potential applications in perovskite solar cells.